Promoting pre-service English teachers’ technological awareness in ELT: narratives from a border area of Indonesia - Lita Liviani Taopan; Renol Aprico Siregar (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
The need for preparing quality teachers with all essential technological competencies is considered crucial. The present study aims to analyze and reveal how a design activity could raise the technology awareness of pre-service English teachers for language teaching. Taking a case in a border area of Indonesia, this study was qualitatively conducted as a narrative inquiry research model. Data were collected through participatory observation, in-depth interview, and written narrative from a lecturer’s journal. Fifteen pre-service English teachers of a university located in East Nusa Tenggara Indonesia were involved in the study. However, only six participants were interviewed to elicit detailed stories about how the activities in ELT media class could promote their technological awareness. Furthermore, thematic analysis with multiple case studies was applied to analyze the data. The results reveal that the pre-service English teachers develop their awareness of the prominence of technology by experiencing the use of technology provided by their lecturer. Furthermore, peer collaboration is essential during the process of developing technological awareness. The findings provide insights for educators and researchers focusing on the technology integration for teaching and learning in remote areas. Further researches highlighting the evaluation of technology integration is needed regarding remote areas.